2021
DOI: 10.1063/5.0048751
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of polarization-induced hole conduction in composition-graded AlInN layers grown by metalorganic chemical vapor deposition

Abstract: This Letter reports the polarization induced hole conduction in composition-graded AlInN epitaxial layers grown by metalorganic chemical vapor deposition. First, the composition-graded AlInN layer with an InN mole fraction from 0.12 to 0.20 was formed on c-plane GaN on sapphire, and they were confirmed to show the p-type hole conduction with a less temperature dependence, which is a feature of polarization-induced carriers. Then, blue light-emitting diodes (LEDs) with the composition-graded AlInN layers insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…
Ternary AlInN alloys are viewed as useful component materials for GaN-based electronic and optical devices, such as barrier layers in heterostructure field-effect transistors (HFETs), [1,2] or cladding layers, [3,4] distributed Bragg reflectors (DBRs), [5,6] and active layers [7,8] in light-emitting devices. For the past several years, we have conducted intensive research on the epitaxial growth and characterization of c-plane AlInN layers with thicknesses of around 300 nm using metal-organic chemical vapor deposition (MOCVD), [9][10][11][12][13][14][15][16][17][18] as primarily aiming at their application to cladding layers in GaN-based visible laser diodes (LDs). Through those studies, we found the following thing.
…”
mentioning
confidence: 99%
“…
Ternary AlInN alloys are viewed as useful component materials for GaN-based electronic and optical devices, such as barrier layers in heterostructure field-effect transistors (HFETs), [1,2] or cladding layers, [3,4] distributed Bragg reflectors (DBRs), [5,6] and active layers [7,8] in light-emitting devices. For the past several years, we have conducted intensive research on the epitaxial growth and characterization of c-plane AlInN layers with thicknesses of around 300 nm using metal-organic chemical vapor deposition (MOCVD), [9][10][11][12][13][14][15][16][17][18] as primarily aiming at their application to cladding layers in GaN-based visible laser diodes (LDs). Through those studies, we found the following thing.
…”
mentioning
confidence: 99%